Factors associated with employment of powered wheelchair users. - Tederko, Piotr; Frasuńska, Justyna; Bobecka Wesołowska, Konstancja; Wesołowski, Krzysztof; Czech, Julita; Gawlak, Dominika; Tarnacka, Beata (Disability & Rehabilitation: Assistive Technology, 2024)
Purpose: To identify correlations between demographic, health-related, environmental factors and the employment status of power wheelchair (PWC) users. Method: We retrospectively analysed semi-structured interviews with 128 participants, their assistants or family members, and the participant's provided medical records. Participants were adult PWC users who applied for grants in purchasing a new PWC for gaining or keeping employment between 2019–2021 in Mazovian Province, Poland. Results: Forty-six PWC users (35.9%) were employed while applying for the financial support programme. Fischer's Exact Test of Independence identified positive correlations between employment and education level (p < 0.001), residing in an urban area (p = 0.02), being employed before starting PWC use (p < 0.001), having vocational rehabilitation (p < 0.001), and living in a relationship (p = 0.002). There were no associations between employment status and sex, age at study entry, age at disability onset, living alone or with others, duration of PWC use, or full or part-time PWC use. Our findings indicate that PWC users are at risk of non-employment and financial hardship. This research may support policies for PWC provision that would support gainful employment. The results show that access to quality education, vocational rehabilitation, and perhaps the physical/emotional support from others in close relationships matter. These aspects should be considered in educational policies, transportation, and physical environmental accessibility for PWC users, supporting their gainful employment. IMPLICATIONS FOR REHABILITATION: Paid employment is recognised for its positive impact on the financial situation, health, and overall life satisfaction of power wheelchair users. Rehabilitation professionals can play a crucial role in facilitating the attainment and maintenance of employment throughout the clinical process. Educating power wheelchair users with factors conducive to supporting their employment, such as pursuing advanced education, utilising vocational rehabilitation services, residing in urban areas, fostering meaningful social relationships, and drawing upon previous employment experiences, may improve outcomes. Sex, age, disability cause, duration of disability, and reliance on a power wheelchair as the primary mode of mobility were found to be unrelated to employment status among power wheelchair users. Further investigation into the needs of the power wheelchair user population in their pursuit of gainful employment is justified.